O papel das argininas alfa-92 e alfa-141 na regulação das propriedades funcionais de hemoglobinas por íons cloreto - Tosquij, Priscilla [UNESP] (FapUNIFESP (SciELO), 2010)
The oxygenation of human Hb (HbA) demands a three state model: two deoxy states To and Tx, free and complexed with anions respectively, and an oxy R state. The regulation between these states is modulated by the presence of anions, such as chloride, that binds to T state. The b inding if chloride, however, remains controversial. The aim of this work is the study of arginines 92a (a1ß2 interface) and 141a (C-terminal) as chloride binding sites. To investigate that, we have studied 92 and 141 site directed mutant species: natural mutants Hb J-Cape-Town (R92Q), desArg (R141Δ), Chesapeake (R92L), and the constructed Chesapeake desArg (R92L,141Δ). We expressed Hbs in Escherichia coli and purified. Through oxygen binding curves we measured affinity and cooperativity, in function of water effect and Bohr effect in presence and absence of chloride. Structural features were obtained through 1H NMR spectroscopy Oxygen binding properties and Bohr effect measured indicated a higher affinity and lower cooperativity in absence and presence of chloride for all mutants. Structural changes represent functional aspects of mutant Hbs, such as a significant rise in affinity or a change in cooperativity. Water activity studies conducted as a function of chloride concentration showed that the only Hb desArg follows the thre state model. The other mutant Hbs do not exhibit the Tx state, a fact confirmed by the number of water molecules bound to each Hb during the deoxy-oxy transition. This behavior suggests that the Arginine 92 site could be responsible for chloride binding to Hb, since oxygenation of 92 mutant Hbs cannot be adjusted by the three state model. However, Bohr effect showed that all mutant Hbs released~1 proton in chloride presence, different from HbA that releases ~2, suggesting a role for 141 arginine in the tertiary and quaternary Bohr effect.
The role of alpha-92 and alpha-141 arginines in the hemoglobin functional properties regulated by chloride ions
Keywords: Allosteric regulation; Binding sites; Erythrocytes; Oxygenation